Autonomy of the Federal Organizational Units - Reto Steiner; Etienne Huber (Yearbook of Swiss Administrative Sciences, 2012)
This article, which is based on a written survey of all organizational unit managers of the Swiss Federal Government, shows the structure and steering of all organizations on the federal level and the factors that influence autonomy. The survey indicates that the formal guidelines on autonomy, as modeled by legal form and organizational type, as well as the organization of leadership structures (e.g., appointment of a supervisory body), are congruent with actual autonomy. This finding is not surprising in a country having a clear tradition as a constitutional state (Rechtsstaatstradition), nevertheless in international comparison where the granting of autonomy is more strongly shaped by governmental preferences, it is not self-evident.